1990
DOI: 10.1111/j.1442-200x.1990.tb00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and Abdominal Arterial Hemodynamics in Preterm Infants with Patent Ductus Arteriosus

Abstract: Using Doppler echocardiography we evaluated the effect of ductal shunt flow on the cerebral and abdominal arterial blood flow in 25 preterm infants. Eligible for inclusion in this study were healthy preterm newborn infants. They were divided into two groups based on their gestational age: group A, 33‐36 weeks (15 infants) and group B, 28–32 weeks (10 infants). Two‐dimensional Doppler echocardiograms were obtained in each infant during the first 8 hours of life and repeated every 6–12 hours until no ductal shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…They have shown decreased flow and increased vascular resistance with a resultant reduction in cerebral perfusion, associated with an indomethacin bolus or infusion over 30 min [see [13][14][15]. Recently Lemmers et al [7] found no significant reduction in regional cerebral oxygen saturation (r c SO 2 ) and no significant increase in the fractional cerebral tissue oxygen extraction (FT c OE) after indomethacin administration over a period of 1 h. We felt that the current study could add to our understanding of the physiological, possibly protective, response to the reduced cerebral perfusion seen when administering indomethacin over a period of 30 min to preterm babies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown decreased flow and increased vascular resistance with a resultant reduction in cerebral perfusion, associated with an indomethacin bolus or infusion over 30 min [see [13][14][15]. Recently Lemmers et al [7] found no significant reduction in regional cerebral oxygen saturation (r c SO 2 ) and no significant increase in the fractional cerebral tissue oxygen extraction (FT c OE) after indomethacin administration over a period of 1 h. We felt that the current study could add to our understanding of the physiological, possibly protective, response to the reduced cerebral perfusion seen when administering indomethacin over a period of 30 min to preterm babies.…”
Section: Introductionmentioning
confidence: 99%
“…These relate to the timing of treatment, the drug to be used, its dosage and mode of administration. 'Ductal steal' is regarded as an independent cause of reduced cerebral (and other end organ) perfusion [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…13 With regard to the central nervous system, although some investigators have reported no change in cerebral blood flow (CBF) as a result of compensatory increase in cardiac output, 14 most studies have found CBF to be impaired in preterm infants with a PDA. [15][16][17][18][19] Doppler studies have shown that the negative effect of PDA on CBF mainly affects the blood flow during diastole, as evidenced by a decrease in flow velocity and increase in pulsatility or resistance index. Similarly, near-infrared spectroscopy and superior vena cava flow studies have demonstrated and suggested, respectively, a reduced CBF in the presence of a hemodynamically significant PDA.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms include decreased peripheral organ perfusion and increased pulmonary perfusion [8][9][10] . Clinical evaluation of PDA, either by auscultation or by palpation of pulses, is of limited value and in the extremely low birth weight neonate, Doppler flow echocardiography is required to confidently confirm or refute the diagnosis of PDA [11] .…”
mentioning
confidence: 99%